Preclinical studies of a Pro-antibody-drug conjugate designed to selectively target EGFR-overexpressing tumors with improved therapeutic efficacy - Yang, Yun (MAbs, 2016)
Antibody-drug conjugates (ADCs) have exhibited potent clinical benefits in cancer therapy. However, development of ADCs against epidermal growth factor receptor (EGFR) has limitations because of wide expression of EGFR in both normal and tumor tissues. Previously, we developed an anti-EGFR protease-activated antibody (pro-antibody), termed as PanP, which remains inert against EGFR until activated by tumor-specific protease. Herein, we for the first time report a new class of pro-antibody-drug conjugate (PDC) against EGFR, denoted as PanP-DM1. It has been designed to selectively target the EGFR-overexpressing tumor cells and exert greater anti-tumor activity compared with PanP. Our data showed that PanP-DM1 also could be selectively activated by tumor-specific protease 'uPA'. Furthermore, activated PanP-DM1 was potently cytotoxic against EGFR-overexpressing tumor cell lines in vitro. Crucially, our data indicated that PanP-DM1 was significantly more effective in eradicating EGFR-overexpressing tumors in vivo. Additionally, toxicity was preliminarily evaluated in mice as measured by body weight loss. In summary, our study suggests that PanP-DM1, a novel pro-antibody-drug conjugate, has cancer-selectivity, efficacy and safety profile that supports its potential use for EGFR-overexpressing tumors.